The role of nurse-client relationships in maternal and child healthcare: a qualitative study in rural Tanzania - Isangula, Kahabi; Mwasha, Loveluck; Pallangyo, Eunice; Ndirangu-Mugo, Eunice (Frontiers in Health Services, 2023)
Background: The literature suggests that poor provider-client relationships in maternal and child healthcare (MCH) continue to impact healthcare service uptake, continuity of care, and MCH outcomes. However, there is a paucity of literature on the benefits of the nurse-client relationship for clients, nurses, and the health system, particularly in rural African contexts. Objective: This study examined the perceived benefits of good and disadvantages of poor nurse-client relationships in rural Tanzania. We present the findings of a community-driven inquiry that was the first step of a broader study that sought to co-design an intervention package for strengthening nurse-client relationships in MCH in rural contexts using a human-centred design approach. Methods: This study used a qualitative descriptive design. Nine focus group discussions and 12 key informant interviews were conducted using semi-structured interview guides. Participants were purposefully selected nurses/midwives and clients attending MCH services, and MCH administrators. Data were managed using NVivo and analyzed thematically. Results: A range of perceived benefits of good nurse-client relationships and disadvantages of poor relationships emerged. Perceived benefits of good nurse-client relationships included: (i) benefits to clients (increased healthcare-seeking behaviours, disclosure, adherence, return to care, positive health outcomes, and referral tendencies); (ii) benefits to nurses (increased confidence, efficiency, productivity, job satisfaction, trust, and community reputation and support); and (iii) benefits to healthcare facilities/systems (increased client load and consequently income, fewer complaints and legal disputes, increased trust and facility delivery, and reduced maternal and child deaths). The disadvantages of poor nurse-client relationships were basically the opposite of their benefits. Conclusion: The benefits of good nurse-client relationships and the disadvantages of poor relationships extend beyond patients and nurses to the healthcare system/facility level. Therefore, identifying and implementing feasible and acceptable interventions for nurses and clients could pave the way for good nurse-client relationships, leading to improved MCH outcomes and performance indicators.